Reconfiguration decision making based on artificial intelligence technology in cognitive radio networks - Qian HE; Zhi-yong FENG; Ping ZHANG (Tongxin xuebao)
Cognitive wireless networks introduced the reconfiguration technologies to achieve the dynamically time-varying adaptation of the environment.A reconfiguration decision making model and reconfiguration decision algorithm based on the artificial intelligence technology were presented.The reconfiguration decision algorithm,which include the reasoning and learning process with the help of the cognitive capabilities of awareness,reasoning and learning,could achieve adaptation of the environment and also maintain and enhance the system performance.